Building a training program to develop the performance of kindergarten teachers and measuring its impact on developing the Speaking skills of kindergarten children for the Republic of Yemen - Al-Jamrah, Zakiah Mohammed Ali (Journal of Educational and Psychological Sciences, 2023)
The research aims to develop a training program to improve kindergarten female teachers’ performance and assess the impact of this program on kindergarten children’s development of Speaking skills in Yemen. The researcher developed the training program, designed a note card for the performance of kindergarten female teachers, and tested the Speaking skills of kindergarten children to achieve the research objectives. The data collecting instruments were given to validators specializing in the Arabic language curricula and kindergartens to ensure their validity and reliability. The research sample consists of 25 female teachers and 126 kindergarten children from public schools in the Capital Secretariat (Sana’a) for the academic year 2021–2022. The descriptive and experimental approaches were used in the same group. The findings have revealed statistically significant differences between the means values of the experimental group at the significance level (0.05), both in observing the performance of kindergarten female teachers and in the Speaking skills test of kindergarten children that the result is in favor of the post-application. Such differences are attributed to the impact of the training program on the performance of kindergarten female teachers as well as the development of kindergarten children’s Speaking skills. The researcher recommends that training programs should be built to provide kindergarten and first-grade female teachers with the required language skills and to improve students’ Speaking skills. Such training programs will significantly raise students’ educational level in the future.